TAYANGAN FILM TELEVISI (FTV) PERSPEKTIF PRODUKSI ORGANISASI - Robby Aditya Putra; Dede Mercy Rolando (Universitas Islam Balitar, 2018)
Solid teamwork in producing a television program is a necessity, so that production results are maximum and meaningful. If the production process is not carried out according to the plot, it will certainly have an impact on the program produced. Given the urgency, it is important to examine how the stages of production of the organization in making television films. This research focuses on the production of the organization (FTV)